PENGEMBANGAN MEDIA INTERAKTIF BRAILLE CARD UNTUK MENINGKATKAN KEMAMPUAN MEMBEDAKAN HURUF SISWA TUNANETRA DI SLB ARNADYA - Dewi, Nurainun Sucitra; Syamsuddin, Syamsuddin; Zulfitrah, Zulfitrah (-, 2025)
AbstractThis research was conducted to find out how the level of students' need for learning media, to media, prototypes, validation, teacher responses, and the response of visually impaired students to Braille Card me dia at SLB Arnadya. This research is a Research and Development research with a 4-D development model (Four D Models) consisting of 4 stages: define stage, design stage, development stage and disseminate stage. The data collection technique is by conducting interviews, questionnaires, practicality tests and validity tests. The results obtained are (1) 97% braille card media shows that the media developed is really needed in the learning process. (2) In the results of the research that have been obtained in the first stage of shape dimension validation 3.50%, validation, second stage 3.80%. In the first stage of validation, the content and material dimensions were obtained with a value of 3.90%, the second stage of 4.00%, these results show that the media is very valid for use. (3) The teacher's response to the braille card media obtained a score of 95% while the student's response was 97.5%. This shows that braille card media is very practical to use in the learning process. The results show that braille card media is worthy of use in Extraordinary Schools.Keywords: Braille Card Media, Distinguishing Letters, Blindness, 4D.